Pengaruh Daya Tarik Produk Halal, Harga dan Kepuasan Pelanggan Terhadap Minat Berkunjung Kembali Konsumen Snack di UD. Adi Putra Perkasa - Safitri, Firda Ayu Diah; Wardhani, Rike Kusuma; Kusumawardani, Mawar Ratih (ITB AAS INDONESIA Surakarta, 2024)
UD. Adi Putra Perkasa is one of the businesses established in Kediri City and has been run by Mr. Adi Sucipto since 2014. This business offers various types of products that are traded, ranging from banana chips, breadfruit, banana sale, purple cassava, tofu crackers, allen-allen, elephant ear chips, seblak crackers, spicy marning, savory, potato sticks, basreng, intestinal chips, corn twisko with various kinds of affordable prices among the community. Some customers often judge that the taste of the snack products sold is delicious, savory and the contents in the packaging are more than other sellers. To maintain the interest of revisiting consumers, business owners focus on product attractiveness, price and customer satisfaction which are considered by these three factors to be able to influence consumers' interest in revisiting. The purpose of this study is to determine the influence of product attractiveness, price and customer satisfaction partially or simultaneously on the interest of snack consumers to visit again at UD. Adi Putra Perkasa. The research method is a research with a quantitative approach and 65 respondents as well as quantitative descriptive data analysis techniques. The results of the study showed that there was an influence of product attractiveness, price and customer satisfaction partially or simultaneously on the interest of snack consumers to visit again at UD. Putra Perkasa.